Identification of interferon-stimulated genes with modulated expression during hepatitis E virus infection in pig liver tissues and human HepaRG cells - Meyer, Léa; Duquénois, Isoline; Gellenoncourt, Stacy; Pellerin, Marie; Marcadet-Hauss, Aïlona; Pavio, Nicole; Doceul, Virginie (Frontiers in Immunology, 2023)
Hepatitis E virus (HEV) is a common cause of enterically transmitted acute hepatitis worldwide. The virus is transmitted by the fecal-oral route via the consumption of contaminated water supplies and is also a zoonotic foodborne pathogen. Swine are the main reservoir of zoonotic HEV. In humans, HEV infection is usually asymptomatic or causes acute hepatitis that is self-limited. However, fulminant hepatic failure and chronic cases of HEV infection can occur in some patients. In contrast, HEV infection in pigs remains asymptomatic, although the virus replicates efficiently, suggesting that swine are able to control the virus pathogenesis. Upon viral infection, IFN is secreted and activates cellular pathways leading to the expression of many IFN-stimulated genes (ISGs). ISGs can restrict the replication of specific viruses and establish an antiviral state within infected and neighboring cells. In this study, we used PCR arrays to determine the expression level of up to 168 ISGs and other IFNrelated genes in the liver tissues of pigs infected with zoonotic HEV-3c and HEV-3f and in human bipotent liver HepaRG cells persistently infected with HEV-3f. The expression of 12 and 25 ISGs was found to be up-regulated in infected swine livers and HepaRG cells, respectively. The expression of CXCL10, IFIT2, MX2, OASL and OAS2 was up-regulated in both species. Increased expression of IFI16 mRNA was also found in swine liver tissues. This study contributes to the identification of potential ISGs that could play a role in the control or persistence of HEV infection.